2021
DOI: 10.1155/2021/5521519
|View full text |Cite
|
Sign up to set email alerts
|

Mogroside V Alleviates Lipopolysaccharide-Induced Neuroinflammation via Inhibition of TLR4-MyD88 and Activation of AKT/AMPK-Nrf2 Signaling Pathway

Abstract: As innate immune effector cells in the central nervous system (CNS), microglia not only are essential for the normal development of nervous system but also act on different neurological diseases, including Alzheimer’s disease (AD), Huntington's disease (HD), and other neuroinflammatory diseases. Mogroside V (Mog), a natural plant active ingredient and isolated form of Momordica grosvenori, has been shown to possess anti-inflammatory action, but few studies were carried out to investigate the effects of Mog on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A study indicated DL0410 ((1,1′-([1,1′-biphenyl]-4,4′-diyl)­bis­(3-(piperidin-1-yl)­propan-1-one)­dihydrochloride), a novel dual cholinesterase inhibitor, exerts neuroprotective effects against hippocampus and cortex injury and maintains the blood–brain barrier via mediating of the TLR4/Myd88 signaling pathway . Liu et al reported that mogroside V alleviated lipopolysaccharide-induced neuroinflammation through inhibition of the TLR4/Myd88 inflammation pathway . P53 was reported as the downstream gene of the TLR4/Myd88 inflammation pathway as the p53 expression increased after activation of TLR4/Myd88 signaling by LPS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study indicated DL0410 ((1,1′-([1,1′-biphenyl]-4,4′-diyl)­bis­(3-(piperidin-1-yl)­propan-1-one)­dihydrochloride), a novel dual cholinesterase inhibitor, exerts neuroprotective effects against hippocampus and cortex injury and maintains the blood–brain barrier via mediating of the TLR4/Myd88 signaling pathway . Liu et al reported that mogroside V alleviated lipopolysaccharide-induced neuroinflammation through inhibition of the TLR4/Myd88 inflammation pathway . P53 was reported as the downstream gene of the TLR4/Myd88 inflammation pathway as the p53 expression increased after activation of TLR4/Myd88 signaling by LPS .…”
Section: Resultsmentioning
confidence: 99%
“…64 Liu et al reported that mogroside V alleviated lipopolysaccharide-induced neuroinflammation through inhibition of the TLR4/Myd88 inflammation pathway. 65 P53 was reported as the downstream gene of the TLR4/Myd88 inflammation pathway as the p53 expression increased after activation of TLR4/Myd88 signaling by LPS. 39 Our study is consistent with a previous report.…”
Section: H Pylori In the Gutmentioning
confidence: 99%
“…Mogroside V (MV) is the major component of mogrosides in the fruit of S. grosvenorii. In vitro studies have demonstrated that MV can alleviate lipopolysaccharide-induced inflammation in cultured cells (Li et al, 2019;Liu et al, 2021). Moreover, we found that MV supplementation in vitro maturation medium can promote porcine oocyte maturation (Nie et al, 2020), alleviate the quality deterioration of in vitro ageing oocytes (Nie et al, 2019), and protect porcine oocytes from meiotic defects induced by LPS (Yan et al, 2021).…”
Section: Introductionmentioning
confidence: 79%
“…Lonicera japonica has been reported to effect the release of inflammatory factors ( tnf-α , il-1β , il-6 and ifn-γ ) through several signaling pathways, such as the IL-17 signaling pathway and the p38/MAPK signaling pathway [ 53 , 54 , 55 ]. According to some studies, Mogroside V is also able to reduce the expression of inflammatory factors such as il-1β , il -6 , and tnf-α , and to inhibit the activation of cox-2 [ 26 , 56 , 57 ]. Glucoraphanin can be transformed into the active substance sulforaphane under the action of human intestinal flora or myrosinase, and sulforaphane can further activate the Nrf2 signaling pathway of human cells to exert an anti-inflammatory effect [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%